Penerapan Analisis Wacana Kritis Norman Fairclough Terhadap Kitab Ta’liim Al-Muata’allim Tentang Interaksi Guru Dan Siswa - Basri, Junaidin; Salamudin, Ceceng; Rozak, Kiki Abdul (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
In the book "Ta’liim al-Muta’allim," teachers are regarded as the most crucial element in the learning process, thus deserving profound respect and adherence. However, excessive reverence can stifle students' critical thinking, fostering intellectual stagnation and a culture of blind conformity (taqlid). Consequently, the interaction between teachers and students becomes imbalanced and skewed. Norman Fairclough's Critical Discourse Analysis (CDA) provides a conceptual framework to address these issues by dissecting the ideological and hegemonic power relations that influence students' cognitive and behavioral responses. The objective of this study is to explore the application of Norman Fairclough's Critical Discourse Analysis to the book "Ta’liim al-Muta’allim" concerning teacher-student interaction. This research is a library study employing a descriptive-analytical method. Data collection was conducted through a literature review, and data analysis was performed using Fairclough's Critical Discourse Analysis on the primary source, "Ta’liim al-Muta’allim," and secondary sources including books, journals, and other written materials aligned with the research objectives. The findings reveal that the concept of teacher-student interaction in "Ta’liim al-Muta’allim" is doctrinaire, non-democratic, and non-dialogical. This is elucidated through Fairclough's Critical Discourse Analysis as follows: There is a social disharmony in its semiotic aspect, positioning the teacher excessively above the student. Overcoming this disharmony is hindered because the Kitab Kuning (traditional Islamic text) is often regarded as a finished and ready-to-use product, and its authors are seen as revered figures who must always be esteemed. The existing social order perpetuates this disharmony, benefiting the teacher in terms of social and cultural hierarchy. The way to address this disharmony is by replacing outdated values that are no longer relevant with new values that are considered more appropriate and beneficial. Keywords: Norman Fairclough’s Critical Discourse Analysis, "Ta’liim al-Muta’allim," Teacher-Student Interaction